Potential factors, including activities of daily living, influencing home discharge for patients with putaminal haemorrhage. Issue 1 (December 2016) - Maeshima, Shinichiro; Okamoto, Sayaka; Okazaki, Hideto; Mizuno, Shiho; Asano, Naoki; Maeda, Hirofumi; Masaki, Mitsuko; Matsuo, Hiroshi; Tsunoda, Tetsuya; Sonoda, Shigeru
Abstract Background Convalescent rehabilitation wards assist stroke patients in acquiring skills for activities of daily living to increase the likelihood of home discharge. However, an improvement in activities of daily living does not necessarily imply that patients are discharged home. We investigated the characteristics of patients with putaminal haemorrhage who are discharged home following convalescence in rehabilitation wards. Methods The sample comprised 89 patients (58 men and 31 women) with putaminal haemorrhage hospitalised in the convalescent rehabilitation ward of our hospital between August 2012 and July 2013. Their age ranged from 29 to 88 years (61.9 ± 11.9 years). The lesion occurred on the right side in 48 and on the left in 41 patients. The mean period from onset to hospitalisation in the convalescent rehabilitation ward was 30.8 ± 17.2 days, and the mean hospitalisation period was 70.7 ± 31.8 days. We examined age, sex, haematoma volume, duration from onset to hospitalisation, neurological symptoms, cognitive function, functional independence measure, number of cohabitating family members and whether the patient lived alone before stroke, and the relationship among these factors and discharge destination (home or facility/hospital) was assessed. Results The discharge destination was home for 71 and a facility or hospital for 18 patients. Differences were observed in age, haematoma volume, neurological symptoms, cognitive function, functional independence measure score on admission and discharge, number of cohabitating family members and whether the patient lived alone before stroke for patients discharged home. Patients who required long-term care and were discharged home were more likely to be living with family members who were present during daytime. Home discharge was possible if functional independence measure score was ≥70 at the time of discharge for motor items and ≥24 for cognitive items, even if a patient lived alone before stroke. Conclusions Although the presence of cohabitating family members was important, the factor most strongly influencing home discharge was the patient's activities of daily living status at the time of discharge. For patients who lived alone before stroke, physical and cognitive functions must be maintained for them to be discharged home after rehabilitation.